2012
DOI: 10.1021/jp300624z
|View full text |Cite
|
Sign up to set email alerts
|

Study of the Fundamental Units of Novel Semiconductor Materials: Structures, Energetics, and Thermodynamics of the Ge–Sn and Si–Ge–Sn Molecular Systems

Abstract: The binary Ge(y)Sn(z) and ternary Si(x)Ge(y)Sn(z) molecular systems containing up to five atoms were investigated by means of density functional theory and coupled cluster calculations. The minimum energy structures were calculated and higher energy isomers are also proposed. The atomization energies of the ground state isomers were calculated by the CCSD(T) method with correlation consistent basis sets up to quadruple-ζ quality. The resulting values were extrapolated to the complete basis set limit and correc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 62 publications
0
2
0
Order By: Relevance
“…Furthermore, in the first step of eq ( Rea – E + SiH 2 Ph 2 → TS1 – E – Si → Int1 – E – Si ), one Si–H bond is broken, and two bonds are formed (E–Si and E–H). It was reported that the bond strengths for E–Si and E–H bonds decrease in the general order (kcal/mol) C–Si (82.7) > Si–Si (76.0) > Ge–Si (70.6) > Sn–Si (55.7) > Pb–Si (31.5) and C–H (92.2) > Si–H (86.0) > Ge–H (78.8) > Sn–H (69.2) > Pb–H (57.8), respectively. Again, these data are consistent with the trend in the first intermediate energy (Δ E Int1 ) for eq .…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, in the first step of eq ( Rea – E + SiH 2 Ph 2 → TS1 – E – Si → Int1 – E – Si ), one Si–H bond is broken, and two bonds are formed (E–Si and E–H). It was reported that the bond strengths for E–Si and E–H bonds decrease in the general order (kcal/mol) C–Si (82.7) > Si–Si (76.0) > Ge–Si (70.6) > Sn–Si (55.7) > Pb–Si (31.5) and C–H (92.2) > Si–H (86.0) > Ge–H (78.8) > Sn–H (69.2) > Pb–H (57.8), respectively. Again, these data are consistent with the trend in the first intermediate energy (Δ E Int1 ) for eq .…”
Section: Resultsmentioning
confidence: 99%
“…28 In later years, progress in studies employing a 3c-4emodel has been confirmed by development in computational studies and quantum physics. 33 The hypervalent bonding of molecules has also been investigated by von Schleyer et. al.…”
Section: -Center-4 Electron Conceptmentioning
confidence: 99%